The effectiveness of gaming interventions for depression and anxiety in young people: systematic review and meta-analysis. Issue 1 (7th January 2022) - Townsend, Christopher; Humpston, Clara; Rogers, Jack; Goodyear, Victoria; Lavis, Anna; Michail, Maria
Abstract : Background: Recent research has investigated the use of serious games as a form of therapeutic intervention for depression and anxiety in young people. Aims: To conduct a systematic review and meta-analysis into the effectiveness of gaming interventions for treating either depression or anxiety in individuals aged 12–25 years. Method: An electronic search was conducted on the 30 March 2020, using PsycINFO, ISI Web of Science Core Collection, Medline and EMBASE databases. Standardised effect sizes (Hedge's g ) were calculated for between-participant comparisons between experimental (therapeutic intervention) and control conditions, and within-participant comparisons between pre- and post-intervention time points for repeated measures designs. Results: Twelve studies (seven randomised controlled trials (RCTs) and five non-randomised studies) were included. For RCTs, there was a statistically significant and robust effect ( g = −0.54, 95% CI −1.00 to −0.08) favouring the therapeutic intervention when treating youth depression. For non-RCTs, using a repeated measures design, the overall effect was also strong ( g = −0.75, 95% CI −1.64 to 0.14) favouring therapeutic intervention, but this was not statistically significant. Interestingly, we found no statistically significant effect for treating youth anxiety. Conclusions: There is preliminary evidence to suggest that gaming interventions are an effective treatment for youth depression, but not anxiety. Further research is warranted to establish the utility, acceptability and effectiveness of gaming interventions in treating mental health problems in young people.